A comparative study to assess the efficacy of oral versus vaginal route of misoprostol in missed first trimester abortion - C. R., Vijaykumar; C., Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of the study to contrast the effectiveness of misoprostol taken oral vs vaginal method, for the management of missed abortion in the early trimester, and to acknowledge misoprostol value in cervical dilatation before any surgical pregnancy termination, Methods: Comparing the efficacy of misoprostol, by vaginal and oral routes, for termination of first trimester missed abortion was conducted in the department of obstetrics and gynaecology, at DR B. R. Ambedkar medical college and hospital, Bangalore. 2 groups were made as group A and group B which had 24 participants in each group and a total of 48 participants, in which group A was given misoprostol 400 mcg orally, maximum up to 3 doses and group B was given misoprostol 400 mcg maximum up to 3 doses and outcome was documented. Primary outcome expecting drug-induced complete expulsion of products of conception (POCs). Secondary outcomes measured were induction expulsion interval, number of doses required, classification of failures, cervical canal permeability in women requiring surgical evacuation, side effects. Results: Both oral and vaginal routes are highly effective (oral=75%, vaginal=91.7%, p=2.400), safe and acceptable with tolerable side effects. The mean time to expulsion was longer (10.55 hours) in the oral than vaginal group (8.09 hours). All unsuccessful cases, 2 in vaginal group and 6 in oral group had permeable cervices prior to surgical evacuation. Most of the side effects were tolerable in both groups. Conclusions: Vaginal route of misoprostol is more effective than oral misoprostol for first trimester missed abortion.